2020
DOI: 10.1002/adma.202005679
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action of Nanoparticles by Lethal Stretching of Bacterial Cell Membranes

Abstract: Nanoparticles (NPs) are heavily used in biomedical, industrial, and commercial applications due to the benefits associated with the specific physical and chemical properties of both the bulk and the nanoscale material. The antimicrobial activity of NPs is widely recognized, but the mechanisms of their underlying toxicity remain unclear despite repeated attempts to establish a structure-function relationship between their physicochemical properties and their interactions with biological systems. [1,2] NP uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 76 publications
0
123
0
1
Order By: Relevance
“…For larger NPs within the size range of 80-100 nm, although they are unable to freely translocate across the bacterial cell membrane, still several studies reported their ability to eradicate bacteria [41][42][43][44][45]. The exact antibacterial mechanism of action for larger NPs remained somewhat obscure, until in a recent study [46] researchers provided evidence for what is known as the mechano-bactericidal mechanism of non-translocating NPs. Their work demonstrated that an increase in the membrane tension of bacterial cells is caused by the adsorption of NPs leading to mechanical deformation of the membrane, and eventually cell rupture and death.…”
Section: Gold Nanoparticles (Aunps) As Novel Antibacterial Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For larger NPs within the size range of 80-100 nm, although they are unable to freely translocate across the bacterial cell membrane, still several studies reported their ability to eradicate bacteria [41][42][43][44][45]. The exact antibacterial mechanism of action for larger NPs remained somewhat obscure, until in a recent study [46] researchers provided evidence for what is known as the mechano-bactericidal mechanism of non-translocating NPs. Their work demonstrated that an increase in the membrane tension of bacterial cells is caused by the adsorption of NPs leading to mechanical deformation of the membrane, and eventually cell rupture and death.…”
Section: Gold Nanoparticles (Aunps) As Novel Antibacterial Agentsmentioning
confidence: 99%
“…The concept behind this approach is in designing antibacterial nanomaterials, with a specific nanostructure geometry capable of applying deadly mechanical forces to bacterial cells upon contact. This technique was applied in a recent study [46] for quasi-spherical and star-shaped AuNPs, where quasi-spherical nanoparticles showed a better bactericidal action due to a higher interactive affinity, causing greater membrane stretching and rupturing.…”
Section: Pristine Antibacterial Gold Nanoparticles (Without Any External Stimuli or Attached Ligands)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2: A) Schematic illustration of the bilayer formation from a mixture of lipid+oil (DOPC + Squalene) sandwiched between two water droplets: the bilayer forms after drainage of the oil, in 10-15 minutes. 35,36 The resulting bilayer is stable for at least ≈ 0.5 -2 hours. B) Visualization under dark-field microscopy of an horizontal lipid bilayer in the presence of spiky nanoparticles (100 nm diameter).…”
Section: Pore Formationmentioning
confidence: 99%
“…By taking advantage of proper surface chemistry and inherent nanoplasmonic effect, Au-based nanoplatforms achieved photobactericidal activity against both Gram-negative and Gram-positive bacteria through producing ROS [ 183 ]. In fact, AuNPs can directly kill bacteria ( e.g., Pseudomonas aeruginosa and Staphylococcus aureus ) through inducing lethal bacterial membrane-tension alterations [ 184 ]. One of the most representational nanomaterials with intrinsic antibacterial activity is AgNPs which can eradicate broad-spectrum bacteria even including multidrug-resistant strains and have already been developed as antimicrobial dressings for wound management [ 185 , 186 ].…”
Section: Nanotherapeutic Platforms For Sepsis Treatment Through Targementioning
confidence: 99%